Penguatan Kompetensi Aparatur Satpol PP dalam Meningkatkan Kinerja Penegakan Ketertiban dan Ketenteraman Masyarakat - Indra Indra; Dwi Afni Maileni; Rizki Tri Anugrah Bhakti; Edwar Kelvin (Universitas Nurul Jadid, 2026)
Public order and community tranquility are essential prerequisites for social stability and high-quality public services. However, Public Order Agency (Satpol PP) personnel frequently encounter challenges in the field, including community conflicts, limited understanding of regulations, and insufficient persuasive communication skills in carrying out enforcement duties. Therefore, a structured competency-strengthening program is necessary to enhance the professionalism and effectiveness of Satpol PP personnel. This community service program aimed to improve the competencies of Satpol PP officers in regulatory understanding, persuasive communication, conflict management, and field decision-making. The program was implemented through training sessions, case simulations, group discussions, and practical mentoring involving 50 Satpol PP personnel. Evaluation was conducted using pre-tests and post-tests, participatory observations, and performance assessments during the training activities. The results demonstrated significant improvements in participants’ understanding of regulations and enforcement procedures, enhanced persuasive communication skills when interacting with the public, and better abilities to resolve conflicts in a humane and proportional manner. The average participant score increased from 68.4 before the training to 86.7 after the program. In addition, participants showed greater confidence and readiness to perform public order and community tranquility enforcement duties. The program also generated positive impacts on service quality, field coordination, and the institutional image of Satpol PP as a professional, humane, and accountable public agency. This initiative can serve as a sustainable capacity-building model for local government personnel in supporting effective public order and community tranquility management.